2019
DOI: 10.1007/s40093-019-00313-8
|View full text |Cite
|
Sign up to set email alerts
|

Banana peel biochar as alternative source of potassium for plant productivity and sustainable agriculture

Abstract: Purpose Biochar addition to soil is immensely beneficial for increasing plant productivity and C sequestration, attenuating nutrient leaching loss, counteracting heavy metal contamination and organic waste triggered environmental pollution. To understand the sustainable benefits of biochar, two pot experiments were conducted under net house condition in Khulna University, Bangladesh. Methods Biochar was prepared from banana peel waste through slow pyrolysis process under limited oxygen condition. Three lower r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 24 publications
1
12
0
2
Order By: Relevance
“…Documentary review of scientific articles over the last decade has revealed that TPW, PPW and BPW have successfully used as fertilisers for improving soil fertility and enriching soil microbiota thanks to their content of minerals required for the plant's growth. TPW, PPW and BPW have a high content of the most nutritious minerals, mainly phosphorus (P), potassium (K), sodium (Na), iron (Fe), zinc (Zn), manganese (Mn) and copper (Cu) [ 19 , 148 ]. BPW is an organic waste rich in high potassium (K) content compared to TPW and BPW [ 149 ], also other authors have shown that BPW biochar was found to be high in potassium (K) which could be used as potassium (K) fertilizer, therefore, an alternative source of potassium (K) for plants productivity [ 19 ].…”
Section: Tpw Ppw and Bpw Valorisation Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Documentary review of scientific articles over the last decade has revealed that TPW, PPW and BPW have successfully used as fertilisers for improving soil fertility and enriching soil microbiota thanks to their content of minerals required for the plant's growth. TPW, PPW and BPW have a high content of the most nutritious minerals, mainly phosphorus (P), potassium (K), sodium (Na), iron (Fe), zinc (Zn), manganese (Mn) and copper (Cu) [ 19 , 148 ]. BPW is an organic waste rich in high potassium (K) content compared to TPW and BPW [ 149 ], also other authors have shown that BPW biochar was found to be high in potassium (K) which could be used as potassium (K) fertilizer, therefore, an alternative source of potassium (K) for plants productivity [ 19 ].…”
Section: Tpw Ppw and Bpw Valorisation Methodsmentioning
confidence: 99%
“…TPW, PPW and BPW have a high content of the most nutritious minerals, mainly phosphorus (P), potassium (K), sodium (Na), iron (Fe), zinc (Zn), manganese (Mn) and copper (Cu) [ 19 , 148 ]. BPW is an organic waste rich in high potassium (K) content compared to TPW and BPW [ 149 ], also other authors have shown that BPW biochar was found to be high in potassium (K) which could be used as potassium (K) fertilizer, therefore, an alternative source of potassium (K) for plants productivity [ 19 ]. Consequently, BPW biochar is not recommended for soil acidity remediation, but it would certainly reduce calcareous requirements when applied as a potassium (K) fertilizer [ 150 ].…”
Section: Tpw Ppw and Bpw Valorisation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mazac (2016) prepared five different batches of mixed food wastes including vegetables, fruits, leaves and egg shells to produce biochar at a slow pyrolysis temperature condition of 260 °C for 3 and 6 h and tested them with tomato plants (Solanum lycopersicum) over 30 days. Similarly, Islam et al (2019) tested banana peel biochar produced at 400 °C for 2 h duration and tested it at 1, 2 and 4% loading with Ipomoea aquatica. Although both experiments observed improved yield with biochar, neither test showed statistically significant differences.…”
Section: Optimum Conditions To Biochar As a Soil Amendmentmentioning
confidence: 99%